2012
DOI: 10.1007/s11135-012-9662-y
|View full text |Cite
|
Sign up to set email alerts
|

Dropout in secondary education: an application of a multilevel discrete-time hazard model accounting for school changes

Abstract: For several decades, researchers have focused on dropout in search for an explanation and prevention of this phenomenon. However, past research is characterized by methodological shortcomings. Most of this research was conducted without considering the hierarchical structure of educational data and ignored the longitudinal path towards dropout. Moreover, research that did take into account these shortcomings, did not correct for student mobility between schools, despite the strong correlation with dropout (Sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…First, there is an extensive literature correlating characteristics of students to early school leaving (ESL). For instance, it has been argued that boys, students retained in grade, students with a low socio‐economic status or from ethnic minorities, and little‐engaged and low‐performing students are more likely to leave school before obtaining a qualification (for an overview see Alexander, Entwisle, & Kabbani, ; Lamb, 2011b; Lamote, Van Damme, Van Den Noortgate, Speybroeck, Boonen, & de Bilde, ; Nevala & Hawley, ; Rumberger, ; De Witte et al ., ). This article differs from the earlier literature by focusing on country characteristics rather than on student‐specific elements.…”
Section: Introductionmentioning
confidence: 99%
“…First, there is an extensive literature correlating characteristics of students to early school leaving (ESL). For instance, it has been argued that boys, students retained in grade, students with a low socio‐economic status or from ethnic minorities, and little‐engaged and low‐performing students are more likely to leave school before obtaining a qualification (for an overview see Alexander, Entwisle, & Kabbani, ; Lamb, 2011b; Lamote, Van Damme, Van Den Noortgate, Speybroeck, Boonen, & de Bilde, ; Nevala & Hawley, ; Rumberger, ; De Witte et al ., ). This article differs from the earlier literature by focusing on country characteristics rather than on student‐specific elements.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have examined dropout employing discrete time hazards models (Bowers, 2010; Lamote et al, 2013). This analytic approach extends earlier work by using a large sample in which an intervention was implemented in a “real world” setting, applying propensity score weights, and taking into account school attendance, as recommended by standards.…”
Section: Discussionmentioning
confidence: 99%
“…A factor that has received less attention until recently is that school itself may contribute to failure (de Witte & Rogge, 2013). Inability to detect early warnings, insufficient provision of individual support, neglect of bullying, and in some cases even discrimination against or harassment of students by staff are school-related factors that have been shown to contribute to truancy and poor academic results (Cornell et al, 2013;Elffers, 2012;Lamote et al, 2013). Higher proportions of students of migrant and ethnic minority backgrounds leave school without complete grades than other students, but several studies have shown that socio-economic conditions strongly contribute to such differences (Elffers, 2012;Lundahl & Lindblad, 2018).…”
Section: Notes On School Failure Dropout and School-to-work Transitionsmentioning
confidence: 99%